Kajian Kualitas Air Tanah Ditinjau dari Parameter pH, Nilai COD dan BOD pada Desa Teluk Nilap Kecamatan Kubu Babussalam Rokan Hilir Provinsi Riau - Arief Yandra Putra; Putri Ade Rahma Yulia (Jurnal Riset Kimia, 2019)
Based on a preliminary study that has been carried out, Teluk Nilap Village, Kubu Babussalam District, Rokan Hilir was affected by the disposal of waste from oil company. The waste partly seeps into the residents' water sources which are used for domestic activities. It was because the location of the water sources close to the location of the waste oil disposal. The sampling technique in this study used the observation point technique (pumping test). Sampling refers to the point of waste oil flow (upstream, middle, downstream) and dug well water taken randomly (random sampling). The results showed pH values ranged from 2.8 to 6.6; BOD values range from 0.42 to 141.1 mg / L; COD values range from 20 to 291 mg / L. Ground water quality at some point in Teluk Nilap Village exceeded quality standard limits allowed and included in heavy pollution category.